2008
DOI: 10.1021/np070446u
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial C-Geranylflavonoids from Paulownia tomentosa Fruits

Abstract: Eight C-6-geranylflavonoids ( 1- 8) were isolated from an ethanol extract of Paulownia tomentosa fruits. Tomentodiplacone ( 1), 3'- O-methyl-5'-hydroxydiplacone ( 2), 3'- O-methyl-5'- O-methyldiplacone ( 3), and tomentodiplacone B ( 4) were obtained as new compounds, and 3'- O-methyldiplacol ( 5) was isolated for the first time from a natural source. The structures of these new compounds were determined by using mass spectrometry (including HRMS) and 1D and 2D NMR spectroscopy, and the absolute configurations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
(54 reference statements)
5
45
1
2
Order By: Relevance
“…subtilis , Enterococcus faecalis , Listeria monocytogenes , and S . aureus with MIC values of 2–4 μg/ml (Šmejkal et al, ). It has also been demonstrated that abyssione‐V 4′‐O‐methyl ether ( 88 ) from the stem bark of Erythrina caffra inhibit activity of E .…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…subtilis , Enterococcus faecalis , Listeria monocytogenes , and S . aureus with MIC values of 2–4 μg/ml (Šmejkal et al, ). It has also been demonstrated that abyssione‐V 4′‐O‐methyl ether ( 88 ) from the stem bark of Erythrina caffra inhibit activity of E .…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…aureus , and S . epidermidis with MICs ranging from 2 to 4 μg/ml (Šmejkal et al, ). The MIC value of quercetin 3‐O‐methyl ether ( 101 ) isolated from Cistus laurifolius flowers was found to be 3.9 μg/ml against Helicobacter pylori (Ustün, Ozçelik, Akyön, Abbasoglu, & Yesilada, ).Some researchers have reported synergy between naturally occurring flavane‐3‐ols and antibiotic agents.…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silybin (silibinin, silymarin) has shown antiviral activity against hepatitis C virus [63] and chikungunya virus [64]. C -geranylated flavanones from Paulownia tomentosa fruits have shown antibacterial [65, 66], cytotoxic [67], and anti-inflammatory [68] activities as well as SARS-CoV protease inhibitory activity [69]. Diplacone showed excellent docking properties with DENV MTase (Table 3 ) and both 3ʹ- O -methyldiplacone and 3ʹ- O -methyldiplacol docked well with the ATP site of DENV helicase (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The structures of known isolates were elucidated on the basis of their spectroscopic analysis ( 1 H-, 13 C-NMR, and electrospray ionization (ESI)-MS) by comparison with those of published data. Ten known compounds were determined to be 3′-O-methyl-5′-hydroxydiplacone (2), 14) diplacol (3), 15) diplacone (4), 15) 3′-O-methyldiplacol (5), 15) 6-geranyl-4′,5,7-trihydroxy-3′,5′-dimethoxyflavanone (6), 7) mimulone B (7), 16) dihydrotricin (8), 8) 5,7-dihydroxy-3′,4′,5′-trimethoxyflavanone (9), 17) (+)-pinoresinol (10), 18) and (+)-dehydrovomifoliol (11), 19) respectively (Fig. 1).…”
mentioning
confidence: 99%